2012
DOI: 10.1371/journal.pone.0044533
|View full text |Cite
|
Sign up to set email alerts
|

Case-Control Study of the Etiology of Infant Diarrheal Disease in 14 Districts in Madagascar

Abstract: BackgroundAcute diarrhea is a major cause of childhood morbidity and mortality worldwide. Its microbiological causes and clinico-epidemiological aspects were examined during the rainy seasons from 2008 to 2009 in 14 districts in Madagascar.MethodsStool specimens of 2196 children with acute diarrhea and 496 healthy children were collected in a community setting. Intestinal parasites were diagnosed by microscopy and bacteria by culturing methods. Rota-, astro and adenoviruses were identified using commercially a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
41
2
1

Year Published

2013
2013
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 15 publications
7
41
2
1
Order By: Relevance
“…The detection rate of at least one enteric pathogen was significantly higher in diarrhea cases than in healthy controls, which showed a wide range of pathogens involving bacteria, and similar results have also been obtained from other countries [29, 30]. Although bacteria and parasites were the prominent enteropathogen in acute diarrheal cases aged more than 5 years in some developing countries [31], to our surprise, viral pathogens (RVA and NoV) were the most common pathogen in present study.…”
Section: Discussionsupporting
confidence: 83%
“…The detection rate of at least one enteric pathogen was significantly higher in diarrhea cases than in healthy controls, which showed a wide range of pathogens involving bacteria, and similar results have also been obtained from other countries [29, 30]. Although bacteria and parasites were the prominent enteropathogen in acute diarrheal cases aged more than 5 years in some developing countries [31], to our surprise, viral pathogens (RVA and NoV) were the most common pathogen in present study.…”
Section: Discussionsupporting
confidence: 83%
“…There was a weak association between C T values and disease (P ϭ 0.03), but an independent association could not be confirmed in the multivariate analysis. Previous studies in sub-Saharan Africa also reported similar detection rates for children with and without diarrhea, but in general the rates were lower than we observed (37,38,49), a difference that might be explained by the lower sensitivity of culture versus PCR (11).…”
Section: Discussioncontrasting
confidence: 48%
“…Whereas some agents (norovirus GII and rotavirus) were found mainly among patients, others were found at high rates also among asymptomatic controls. The latter group included ETEC, Shigella, and Campylobacter, which previously have been found at significant rates among children without diarrhea (3,10,16,(36)(37)(38). These findings suggest substantial exposure to enteric pathogens in the study population, probably due to poor sanitation.…”
Section: Discussionmentioning
confidence: 52%
“…Co-infections in children under five in Madagascar were assessed in a recent report; however, they only documented co-infections between bacteria and parasites or viruses [17]. Given the paucity of data on rates of co-infection with multiple enterobacteria, it is difficult to say whether our data are within the expected range, and certainly this is an area needing further investigation.…”
Section: Discussionmentioning
confidence: 91%